FRAMING BERITA AKSI BELA ISLAM JILID II DI REPUBLIKA.CO.ID DAN TEMPO.CO - Misroji; Gustita Akhirani Hasibuan (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
The goal of this study is to determine the type of news framing on Republika.co.id and Tempo.co.id regarding the Action of Defending Islam, Volume II. Data collection was carried out by collecting texts related to the Action of Defending Islam Volume II on Republika.co.id and Tempo.co within the time range of November 1, 2016 to November 31, 2016, which were then analyzed using Zongdang Pan and Gerald M. Kosicki's framing theory. The conclusion of the study is that differences in framing exist in the selection of the lead, headline, news sources, sentences, word choices, and image selection that reinforce the form of news framing. Tempo.co tends to blow up the commotion that occurred between the action's masses and the authorities, while Republika tends to see the positive side of the action and does not blow up the commotion that occurred too much